Pengaruh Sikap Terhadap Keputusan Pembelian Pada Toko Mebel Iwan Serdang Bedagai - Yani Restiani; Fitrianingsih; Sinaga, Eka Mayastika (Sekolah Tinggi Ilmu Ekonomi Bina Karya, 2022)
Furniture is one of the important needs in a household. Various household furniture such as beds, wardrobes, chairs and others are one of the needs that need to be met. This study aims to analyze the effect of consumer attitudes on purchasing decisions at Iwan's furniture store. This research is a field research with a quantitative approach with data analysis techniques carried out with the help of SPSS software. A total of 60 consumers were selected as research respondents. The data analysis technique used simple linear regression and the hypothesis test that was carried out was a partial test (t test). The results showed that attitude has a positive and significant impact on purchasing decisions at Iwan's furniture store.